(untitled) - Brigham, Eugene F. (Mason, OH, 2007)
This comprehensive text from the renowned author team Brigham/Daves keeps the reader first in finance with a full understanding of the conceptual theories and practical skills that lead to stronger financial decisions
Keywords: Business enterprises,Corporations,Hoạt động kinh doanh,Tổ chức kinh doanh; Finance,Finance,Tài chính,Tài chính